Hanifa Sukma 17510005 Jurnal IMPLEMENTASI COOPERATIVE LEARNING TIPE JIGSAW BERBASIS GOOGLE MEET DALAM MENINGKATKAN PRESTASI BELAJAR PPKn POKOK BAHASAN NILAI-NILAI PANCASILA KELAS XI SMA N GONDANGREJO DI MASA PANDEMI COVID-19 TAHUN PELAJARAN 2020/2021: IMPLEMENTASI COOPERATIVE LEARNING TIPE JIGSAW BERBASIS GOOGLE MEET DALAM MENINGKATKAN PRESTASI BELAJAR PPKn POKOK BAHASAN NILAI-NILAI PANCASILA KELAS XI SMA N GONDANGREJO DI MASA PANDEMI COVID-19 TAHUN PELAJARAN 2020/2021 - Hanifa Sukma Hanifa Sukma; Anita Trisiana; Wartoyo Wartoyo (Prodi PPkn Universitas Slamet Riyadi, 2022)
ABSTRACTThe purpose of this study is to know the application of the results and factors in the inventor yof cooperative learning of google meet based jigsaw type in improving the achievement oflearning outcomes of PPKn. Subjects Pancasila Class XI SMAN Gondangrejo in pandemicpomemi Covid-19 years lesson 2020/2021. The type of research in qualitative research usingdescriptive approach. The subjects studied were the mp and the study of the class of educationclass and the study of XI class. Data mining research using interviews, The observation anddocumentation. The result of the study are the Covid-19 period of the Covid-19 pandemicthat encourage learners to be particularly generous in their learning, using the google meetmethod of cooperative learning , the cooperative learning type jigsaw meet, they can beconsistent with specifically off civic education on the subject of Pancasila. Which is acomplex enough subject for students to understand.Key word : Cooperative Learning Tipe jigsaw, Google Meet, Study achievement.